Economic Growth, Financial Development, Income Inequality and Poverty Relationship: An Empirical Assessment for Developing Countries - Ali, Majid; Tariq, Muhammad; Khan, Muhammad Azam (iRASD Journal of Economics, 2022)
The paper contributes to the current literature by investigating the effects of economic growth, income inequality, and financial development on poverty for fifteen (15) developing countries. Panel data over the period from 2002 to 2018 has been used. Pooled Mean Group (PMG) technique has been applied for estimating the results. The study employs panel unit root tests namely: LLC and IPS for checking the unit root in the data. The long results show that all variables turned significant in the model. The income inequality shows positive relationship with poverty. Financial development and economic growth reveal adverse impact on poverty. Government spending and employment (increase in labor force participation) impact on poverty are negative. Furthermore, trade openness and inflation coefficients turned significant however, its sign are not according to the theory. Moreover, in the short run income inequality and economic growth show no impact on poverty. Financial development relationship with the poverty is still positive. Inflation revealed positive relationship with poverty. Trade openness show positive relationship with poverty. And other two variables government spending and labor force participation rate coefficients remained insignificant. The error correction coefficient i.e. speed of adjustment parameter is - 0.089. On the basis of the findings it is suggest that effective policies for boosting up economic growth, advancement of financial sector and reducing income inequality can significantly contribute towards the poverty reduction in the developing countries. It is suggested that the government shall formulate appropriate policies for the development of financial sector, boosting up economic growth and reduction of income inequality which will contribute to the reduction in poverty of the selected countries.